A survey on concomitant common bile duct stone and symptomatic gallstone and clinical values in Shiraz, Southern Iran - Seyed Vahid Hosseini; Abbass Ayoub; Abbas Rezaianzadeh; Ali Mohammad Bananzadeh; Leila Ghahramani; Salar Rahimikazerooni; Hajar Khazraei (Advanced Biomedical Research, 2016)
Background: Common bile duct stone (CBDS) as a result of gallstone is one of the gastrointestinal disorders. In this study, the incidence of CBDS and symptomatic gallstone in Shiraz were investigated, and their management suggested. Materials and Methods: This is a retrospective study that enrolled among 560 patients. The incidence of gallstone together with CBDS was evaluated using an ultrasonography studyand clinical data in the period between March 2014 and 2014 in Shiraz. Comparison between data was done using Student's t-test or Chi-square test. Results: Of these patients, 18.6% were male, and 81.4% were female with a mean age of 47.67 ± 0.74 years. The concomitant rate of gallstone and CBDS was 8.6%. 6.8% of patients with concomitant of gallstone and CBDS showed symptoms while 1.8% had not been diagnosed before the operation. The mean of serum alkaline phosphatase level in patients with the only gallstone was 255.80 IU/L and patients with concomitant gallstone, and CBDS was 580.88 IU/L with a significant difference between two groups (P < 0.001). Furthermore, liver function tests (aspartate aminotransferase, alanine transaminase) showed a significant difference between two groups of patients (P < 0.01, P< 0.001). Conclusions: Clinical variables such as tenderness, fever, and Morphy sign were more severein patients with concomitant gallstone and CBDS. The concomitant rate of gallstone and CBDS in our society is less that Western countries and asymptomatic patients showed fewer ratios than other countries. We think the approach for asymptomatic CBDS patients with gallstone can be affected by our results.